Comparison of single and double impact damage on carbon/epoxy laminates subjected to hygrothermal ageing - Mokhtar, Hanan; Sicot , Olivier; Rosseau, Jerome; Aminanda, Yulfian; Aivazaddeh, Shahram (2012)
This paper studies the effect of impact damage on carbon/epoxy laminates which have undergone hygrothermal ageing. Three stratifications have been chosen whereby the first layup is the classical type used in the industry and the other two are of quasi-isotropic/quasi-homogeneous properties consisting fibres orientated at ±45°and ±60°. The specimens were aged at 70°C with a relative humidity of 85% in a climatic chamber up to 2100h and impacted directly after exiting the climatic chamber. Ultrasonic C-scan was used to analyse the damage before the specimens were placed back into the climatic chamber for the second phase of ageing and the second impact test.